The Correlation between Smartphone Addiction Level and The Psychosocial Development of School-Age Children in Agricultural Areas - Latifah, Aurora Anastasya; Rahmawati, Ira; Rahmawati, Iis (Al-Hijrah Indonesia, 2023)
Smartphones are a form of technology that is growing rapidly. The use of Smartphones has various impacts on users, especially school-age children. One of the impacts that can occur from using Smartphones on school-age children is the inhibition of psychosocial development. This research was conducted to determine the relationship between the level of Smartphone addiction and the psychosocial development of school-age children in agricultural areas. The method used in this study is by using a cross-sectional approach. Sampling using a simple random sampling technique obtained a sample of 150 respondents. Data collection used the SAS-SV questionnaire and the psychosocial development questionnaire. This study used a relationship test, namely the Kendal-Tau test c. The study results showed that students with Smartphone addiction were in the 106 (70.7%) addiction category and 44 (29.3%) non-addictive categories. While the psychosocial development of children in the abnormal category was 86 (57.3%), the borderline category was 28 (18.7%), and the normal category was 36 (24%). These results show that the p-value obtained is 0.000 or a p-value <0.05. It can be said that there is a relationship between the level of Smartphone addiction and psychosocial development. In addition, the value of strength in both relationships is 0.340. This value is included in the weak category. So, the relationship between the two variables is included in the weak category. Then, the level of correlation shows positive results, namely the higher the level of smartphone addiction, the worse the psychosocial development of children.